Managing memory institutions portals: from HTML to CMS and towards applications in XML for multi-platforms. (2nd September 2008) - Bascones, Pere; Carreras, Cesar
Our research group, called Oliba (http: / /oliba.uoc.edu), has been carrying out different projects for museum portals in the past years. There has been evolution in the cultural operators demands, from static HTML in which they did not want any direct involvement to Content Management Systems (CMSs) for direct administration. Actually, dynamic contents such as agenda, activities or exhibitions have brought about such trends towards a more direct management of the website. It was decided to adapt some free software CMS such PhPNuke or Joomla! in order to avoid the enormous effort that is required for every single new development.